PENGARUH PROFITABILITAS, LIKUIDITAS, DAN GROWTH TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2013-2015) - Sri Sukenti; Nur Hidayati; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2017)
This study aimed to analyze the influence of profitability, liquidity, and growth variables on Corporate Social Responsibility (CSR) disclosure in the annual report of manufacturing companies in Indonesia Stock Exchange (IDX). Data that was used in this research was secondary data and sample was selected with purposive sampling method. The method used to measure CSR disclosure was content analysis. The method of measuring the content analysis was done by providing a checklist on CSR items in the company's annual financial statements. The design of this research was quantitative and sample research from 30 manufacturing companies in Indonesia Stock Exchange (IDX) period of 2013-2015. The analysis model for this research was using multiple linear regression analysis. Based on the results of the research analysis, it could be seen that the profitability and growth variables have a positive effect on CSR disclosure, while the liquidity variables have no positive effect on CSR disclosure.